Availability of Zinc, Copper, Iron, Manganese, and Selenium in Feed Ingredients and Sources in Pigs - Yohan Choi; Junseon Hong; Jihwan Lee; Minju Kim (Agriculture)
This study evaluated the trace mineral availability of zinc (Zn), copper (Cu), iron (Fe), manganese (Mn), and selenium (Se) in major feed ingredients, including corn, wheat, soybean meal (SBM), and fish meal (FM). Additionally, we assessed the bioavailability of these minerals in pigs supplemented with inorganic, organic, and nano-sized forms prepared via hot-melt extrusion (HME). A total of 64 barrows (Yorkshire × Landrace × Duroc crossbreds) with an average initial body weight of 26.61 ± 4.12 kg were housed individually in metabolic cages. Pigs were allocated to eight experimental diets in a completely randomized design, with eight replicates per diet group. The apparent total tract digestibility (ATTD) of Zn and Cu was significantly higher in SBM and FM than in the other ingredients (p < 0.05). SBM exhibited higher ATTD and standardized total tract digestibility (STTD) for Fe and Mn than corn, wheat, and FM (p < 0.05). Corn and wheat demonstrated significantly greater digestibility of Se than SBM and FM (p < 0.05). Supplementation with nano-sized minerals prepared by HME increased the digestibility of Zn and Cu, as well as their concentrations in pigs’ serum and liver, while reducing the fecal excretion of these minerals (p < 0.05). Organic mineral forms significantly enhanced Se bioavailability, improving its digestibility and concentrations in the liver and pancreas compared to the inorganic form (p < 0.05). In growth performance, organic and nano-sized mineral sources significantly improved growth rate without the increase in feed intake (p < 0.05). In conclusion, Zn and Cu from high-protein ingredients such as SBM and FM were more digestible than those from grains. Furthermore, plant-based ingredients, such as corn, wheat, and SBM, exhibited greater digestibility of Fe and Se. Among the trace mineral sources, the organic and HME-nano forms improved the bioavailability of Zn, Cu, and Se, while reducing their fecal excretion, thereby enhancing the efficiency of mineral utilization.